Palaeomagnetism and KAr age of Mesozoic and Cenozoic igneous rocks from Antarctica (Dataset) ... - Valencio, Daniel A.; JoséE. Mendía; Vilas, Juan F. (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeomagnetism and KAr age of Mesozoic and Cenozoic igneous rocks from Antarctica ...